The nanoparticle biomolecule corona: lessons learned – challenge accepted?. (7th October 2015) - Docter, D.; Westmeier, D.; Markiewicz, M.; Stolte, S.; Knauer, S. K.; Stauber, R. H.
<x xml:space="preserve">Abstract</x> Besides the wide use of engineered nanomaterials (NMs) in technical products, their applications are not only increasing in biotechnology and biomedicine, but also in the environmental field.